Data compression in smart distribution systems via singular value decomposition - de,Souza JCS; Lessa,Assis TM; Pal,BC (IEEE Transactions on Smart Grid, 2015)
Electrical distribution systems have been experiencingmany changes in recent times. Advances in metering systeminfrastructure and the deployment of a large number of smartmeters in the grid will produce a big volume of data thatwill be required for many different applications. Despite thesignificant investments taking place in the communications infrastructure,this remains a bottleneck for the implementation ofsome applications. This paper presents a methodology for lossydata compression in smart distribution systems using the singularvalue decomposition technique. The proposed method is capableof significantly reducing the volume of data to be transmittedthrough the communications network and accurately reconstructingthe original data. These features are illustrated by resultsfrom tests carried out using real data collected from meteringdevices at many different substations.